High temperature microwave dielectric and thermochemical properties of waste LixMn2O4 battery cathode materials reduced by moso bamboo. (January 2022) - Lin, Shunda; Liu, Renlong; Guo, Shenghui
Abstract: It is important to effectively and in an environmentally friendly manner, recover metallic elements such as lithium and manganese from waste lithium-manganese batteries. In this work, the changes in the dielectric and thermochemical properties of mixtures of waste Lix Mn2 O4 battery cathode materials and moso bamboo during a microwave heating process were studied in detail using moso bamboo as the reducing agent. The dielectric properties of the mixed materials were measured by the cylindrical cavity perturbation method. The results of the high-temperature reduction process demonstrated that the reduction process could be divided into five temperature ranges (e.g., <120 °C, 120°C–220 °C, 220°C–380 °C, 380°C–600 °C, and >600 °C), and the reduction reaction mainly occurred in the third and fourth stages, especially in the ranges of 300–330 °C and 410–430 °C. The results of the microwave absorption characteristics under different conditions demonstrated that high temperatures were favorable for microwave penetration, and the microwave penetration depth (Dp) was 4 cm at 900 °C. In addition, when the moso bamboo content exceeded 16%, the εr" (effective loss factor) and tan δ (loss angle tangent) of the mixtures suddenly dropped to lower levels by approximately 0.064 and 0.087, respectively. It was also found that when the moso bamboo content was 12%, the mixture had better thermal reduction and microwave dielectric properties. Highlights: The dielectric properties of cathode materials and mixtures for lithium ion batteries were measured for the first time. High-temperature reduction mechanism of cathode materials for lithium-ion batteries by biomass reduction. Application of microwave heating in carbothermal reduction of cathode materials. The thermal reduction of Moso bamboo recycling of spent LiMn2O4 batteries can be divided into five stages. When the content of Moso bamboo is 12%, it has good thermal reduction and microwave dielectric properties.